Making Space for All Body Sizes in Pre-, Peri-, and Post-natal Care in Atlantic Canada: A Patient-Informed Hospital Equipment Inventory - Waugh, Rachel; Bernard, Maxine; Gray, Megan; Chandrasekar, Raashsni; DeClercq, Vanessa; Coolen, Jillian; Hamilton-Hinch, Barbara; Snelgrove-Clarke, Erna; Grant, Shannan (Atlantis, 2026)
Background: Diverse, versatile, and readily accessible equipment is essential for healthcare provision, to maximize care quality, minimize complications, and eliminate weight stigma and discrimination. Hospital equipment inventories (inventories) and audits can be completed by internal or external reviewers and are not always publicly available or subject to peer review, despite hospitals receiving significant public funding for care and research. Objective: The objective of this research was to complete an inventory audit to identify, count, and describe (type, weight capacity) bariatric equipment in nine units/ clinics in the Women’s Building of a maternal-newborn hospital in Atlantic Canada. Methods: Six registered nurses completed inventories using a standardized form, including type and weight capacity of all bariatric equipment, in 2018 and 2021, at nine units/clinic sites within an urban maternal-newborn tertiary care facility in Atlantic Canada. Results: The inventory audits conducted in 2018 and 2021 show that additional bariatric beds, stretchers, and blood pressure cuffs were purchased. Nonetheless, findings agree with existing peer-reviewed literature that show bariatric equipment is lacking in Canadian tertiary care settings. Conclusion: The objective of this project was met, confirming an increase in the availability of specific bariatric inventory between 2018 and 2021; however, the current availability and amount of bariatric equipment is not adequate. This quality improvement initiative highlights a strength of local clinician-researcher efforts, relationships, and engagement with patient-centred implementation science.